Perfil digestivo e metabólico de juvenis de tambaqui, Colossoma macropomum (Cuvier, 1818), alimentados com diferentes teores de proteína e lipídio - Almeida, Luciana Cristina de (2006)
The aim of this work was to investigate the metabolism of juvenile tambaqui (Colosssoma macropomum) fed 4 different protein (35, 30, 25 e 20,5 %) and lipids (4, 8, 11 e 14,5 %) levels in isoenergetic diets. The experiment was carried out in the facilities of the Adaptative Biochemistry Laboratory, located in the Genetics and Evolution Department of the Federal University of São Carlos. Fish growth, hematological parameters, digestives enzymes (unspecific proteases, unspecific lipase and amylase), metabolites (glucose, lactate, piruvate, ammonia, protein, fat acids, triglycerides, amino acids and glycogen), and the enzymes LDH, MDH, GDH, ASAT and ALAT were assayed. The hematological parameters presented no significant alterations. Tambaqui digestive enzymes were responsive to dietary levels of protein and lipids. Fish from the treatments I and II depicted the best growth. In contrast, the lowest one was observed in fish fed with the treatments III and IV. We detected glycolysis, glycogenolysis and lipolysis in livers in accordance the increase of the dietary lipid. It was observed muscular glycogenesis and gluconeogenesis from amino acids and lipolysis to energetic supply in fish fed with high lipid levels. The plasma metabolic profile reflected the function of blood metabolite deliver among the tissues underlining biochemical adaptations due to alterations on the fish feeding. In conclusion, dietary protein and lipid levels induced tambaqui digestive enzymes. The increase of dietary lipid resulted in fish growth decreased, augmented the liver glycolysis and glycogenolysis, increase the muscular glucogenesis and the gluconeogenesis. The fish metabolism seemed to be predominantly lipolitic.